Sur les traces de la Première Guerre mondiale à Bruxelles - Serge Jaumain; Virginie Jourdain; Michaël Amara; Bruno Benvindo; Pierre Bouchat; Eric Bousmar; Arnaud Charon; Thierry Eggerickx; Elisabeth Gybels; Chantal Kesteloot; Olivier Klein; Benoît Mihail; et al. (Brussels Studies)
The hundredth anniversary of World War I has put the spotlight on this period once again. The media coverage of the commemorations is unprecedented and even surprising for a conflict which has remained in the memorial shadow of the even more deadly World War II. While there was every reason to believe that the Great War was only a distant memory, it must also be noted that it is still the object of true curiosity on the part of the general public. The hundredth anniversary has also led to a number of publications, most of which are in keeping with the revival of historical research surrounding World War I for the past twenty years or so. The case of Belgium – the scene of fighting in a territory which was almost completely occupied – has thus been well studied. However, while several recent studies have used Brussels as a framework, a global summary specifically devoted to the capital does not exist. This synopsis thus summarises the material traces and immaterial heritage of the conflict in Brussels. The aim is therefore not to trace the history of Brussels during World War I or to present the latest works on this subject, but rather to answer some simple questions asked by the inhabitants of Brussels today: What remains of World War I in the capital? Who is interested in it, and why? How does this conflict resonate today in Brussels’ memories? How are they reflected in the urban space? In other words, this synopsis reverses the historical temporality to observe the results of the sifting of time.